Barriers to empowerment: Assessment of community-led local development organizations in Pakistan. (July 2017) - Wahid, Abdul; Ahmad, Muhammad Shakil; Abu Talib, Noraini Bt.; Shah, Iqtidar Ali; Tahir, Muhammad; Jan, Farzand Ali; Saleem, Muhammad Qaiser
Abstract: Community-led local development and community-driven development mechanisms are recent development phenomenon's adopted by many developing and developed countries, aimed at improving proactive community participation and quality of life along with social wellbeing of local community. The paper is about the role and severity of different barriers that prevent empowerment and community participation in the development of community led development in Pakistan. This paper initially illustrates the concept of empowerment and itsimportance, and then describes the findings of the project's assessment ofbarriers to empowerment among Citizen Community Boards in Pakistan. Audio-taped, structured, open-ended interviews were conducted with six leaders of Citizen Community Boards, who initiated and implemented the community driven projects. Discussion with respondents wasabout mechanisms of community participation;political and elite control; problems encountered at community level due to elite control; and other issues of capacity building and access to information. Interview results revealed that political interference and elite control hinder community participation at local level. Moreover, it is an obstacle that impedes community participation in local community-led development activities. Building capacity at local level is an important ingredient for sustainable development, as it not only provides local stakeholders with an opportunity to participate in decision-making, but also enables "community ownership", a key component of empowerment. The findings of this study contribute towards greater understanding of developmental issues at local level and will help policymakers to focus on highlighted issues and problems faced by community-led development organizations.